Contents and Foreword of the TAWARIKH Journal, issue of April 2016 - TAWARIKH, Editor Journal (ASPENSI in Bandung, Indonesia, 2016)
This journal, with ISSN 2085-0980, was firstly published on 28 October 2009, in the context to commemorate the Youth Pledge Day in Indonesia. Since issues of April 2016 to date, the TAWARIKH journal has been organized by the Lecturers at the Faculty of Adab and Humanities UIN (State Islamic University) Sunan Gunung Djati in Bandung; and published by Minda Masagi Press as a publishing house owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. This journal is published twice a year i.e. every October and April. For period 2012 to 2017, the TAWARIKH journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia).Bandung, West Java, Indonesia: April 28, 2016.Dr. Setia GumilarHonorable Patron of the TAWARIKH Journal; and Dean of FAH UIN SGD in Bandung, West Java, Indonesia.